Legal Analysis of Providing Mortgage Rights Guarantee to Foreign Bank Creditors : A Study at the Land Office of Batam - Utari Afnesia; Laily Washliaty; Ali Amran; Erniyanti Erniyanti; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to investigate and analyze legally the granting of mortgage rights guarantee to creditors, especially foreign banks (conducted at the Land Office of Batam). The method used is normative legal research utilizing library references and interviews with academic and practitioner experts as research subjects. This study is descriptive, systematically analyzing primary, secondary, and tertiary legal materials along with relevant facts. The conclusion of this research is that the granting of mortgage rights to foreign banks follows the procedures stipulated in Ministerial Regulation No. 5 of 2020 from the Ministry of ATR/BPN. The registration process for mortgage rights is conducted electronically, but foreign banks such as China Banking Corporation Limited must first register through the financial partner application. The main challenges in implementing electronic mortgage rights guarantee primarily stem from legal uncertainties regarding the registration of foreign creditors through the financial partner application managed by the Ministry. Additionally, there are technical challenges due to IT systems that are not yet fully prepared. Improving the quality of human resources is also necessary, given the constraints faced at the land office due to a shortage of personnel, while demand from the public and service users remains high.